Importance of reagent addition order in contaminant degradation in an Fe(ii)/PMS system. Issue 74 (25th July 2016) - Huang, Ying; Wang, Zhaohui; Fang, Changling; Liu, Wenqian; Lou, Xiaoyi; Liu, Jianshe
Abstract : Reagent addition order has a significant effect on the contaminant degradation process in an Fe(II)/PMS system. Abstract : Addition order of reagents in the Acid Orange 7 (AO7) degradation process was investigated by varying the concentration of Fe(ii ), the Fe(ii )/peroxymonosulfate (PMS) molar ratio and stepwise addition of Fe(ii ) and PMS. The importance of addition order of reagents was confirmed and an order of Fe(ii )–PMS to improve the oxidation efficiency was recommended.